Faktor Sosio-Demografi yang Berhubungan dengan Penggunaan Suplemen dan Jamu selama Pandemi: Studi Kasus pada Mahasiswa UNIPMA Tahun 2022 - Puri Ratna Kartini; Desi Kusumawati; Ajeng Probo Kusuma; Agung Prabowo Wisnubroto (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Corona Virus Disease 19 (COVID-19) is a global pandemic declared in 2020 by WHO. The high incidence and death rates of COVID-19 affect human social activities in all countries, including Indonesia. This pandemic has had an impact on various sectors including education. Students are one of the groups prone to contracting COVID-19 from the campus cluster. So it is necessary to strengthen one's immunity by consuming supplements and herbs. This study aims to analyze socio-demographic factors related to the use of supplements and herbs in UNIPMA students.Methods: This research is an analytic observational study (cross-sectional design) in which the researcher conducted indirect interviews using a questionnaire instrument distributed through the media google form. This study involved 361 UNIPMA students using a purposive sampling technique. Then the results of the study were analyzed using the chi square test.Result: Based on statistical tests, the results obtained for the gender variable were p = 0.014, the type of study program variable was p = 0.011, the income variable of both parents was p = 0.679 and the access variable to pharmacies and drug stores was p = 0.193.ConclusionÂ : Based on the research results, it can be concluded that socio-demographic factors related to the use of supplements and herbs in UNIPMA students are gender and type of study program. Meanwhile, socio-demographic factors such as the income of both parents and access to pharmacies and drug stores are not related to the use of supplements and herbs in UNIPMA students.